Transgressive Networks: This Week in Blackness and Resistance through Online Programming - Florini, Sarah (AoIR Selected Papers of Internet Research, 2013)
This paper explores the dynamics of power and resistance surrounding the independent online media network 2 (TWiB). Created by Elon James White, 2 is comprised of six podcasts covering a diverse range of topics, an active blog, and a fully functioning social networking site. White and his co-hosts L. Joy Williams and Aaron Rand Freeman, collectively nicknamed Team Blackness, have gained visibility in the progressive media world and have cultivated a substantial online audience. Despite this, 2 has had difficulty connecting with other media outlets or finding sponsors to support their work. I argue that this is because 2 ’s programming embraces a diverse, heterogeneous, and internally contradictory understanding of “Blackness” that makes it largely incompatible with existing media production and consumption paradigms even in online and independent media spaces.